Navigating Cloud Computing: Exploring Fundamental and Advanced Concepts, Architectures, and Security Mechanisms - Siva Prasad Ponnuru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the evolution and current state of cloud computing, addressing fundamental concepts, advanced architectures, and security mechanisms. The article examines the transformation from traditional infrastructure to modern cloud environments, highlighting key technological advancements in virtualization, containerization, and service delivery models. It investigates critical aspects of cloud security, management mechanisms, and specialized cloud architectures while analyzing various deployment patterns and their implications. The article encompasses technical and operational perspectives, providing insights into infrastructure components, automation strategies, and delivery model considerations. Through a detailed examination of reference architectures, design patterns, and implementation strategies, this study offers a holistic view of cloud computing’s impact on enterprise operations and its role in driving digital transformation.